2015
DOI: 10.1111/ibi.12280
|View full text |Cite
|
Sign up to set email alerts
|

Blood and cloacal swab sampling for avian influenza monitoring has no effect on survival rates of free‐ranging ducks

Abstract: Concerns about the spread of avian influenza viruses (AIVs) have led to cloacal swab sampling of hundreds of thousands of birds worldwide as part of AIV surveillance schemes, but the effects of cloacal swabbing have not been adequately evaluated. We tested for differences between swabbed, swabbed and bled, and non‐sampled wild ducks in terms of live re‐encounter and dead recoveries for Common Pochard Aythya ferina and Tufted Duck Aythya fuligula, and also determined re‐encounter and recovery rates for Mallard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…Although the effect of blood sampling depends on the species, locality, and the episode of selection when samples are taken, our results support those of other studies suggesting few negative effects of blood sampling on within-year reproductive success or survival of adult females (Sheldon et al 2008, Redmond and Murphy 2011, Guillemain et al 2015, Bowers et al 2016, Smith et al 2016. Our inability to detect an effect on adults suggests that collecting blood samples from breeding female Tree Swallows is comparable to that of routine capture and banding, which studies have also shown have little or no effect on birds when implemented properly (Angelier et al 2011, Spotswood et al 2012.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although the effect of blood sampling depends on the species, locality, and the episode of selection when samples are taken, our results support those of other studies suggesting few negative effects of blood sampling on within-year reproductive success or survival of adult females (Sheldon et al 2008, Redmond and Murphy 2011, Guillemain et al 2015, Bowers et al 2016, Smith et al 2016. Our inability to detect an effect on adults suggests that collecting blood samples from breeding female Tree Swallows is comparable to that of routine capture and banding, which studies have also shown have little or no effect on birds when implemented properly (Angelier et al 2011, Spotswood et al 2012.…”
Section: Discussionsupporting
confidence: 88%
“…With the advent of molecular biology and advances in vertebrate physiological ecology, blood sampling has become a standard part of the study protocol for many vertebrate populations, producing a wide array of information on parentage, mating systems, and metabolic, endocrine, and immuno-physiology. Several investigators have examined the possible effects of blood sampling on birds (Sheldon et al 2008, Redmond and Murphy 2011, Guillemain et al 2015, Bowers et al 2016, Smith et al 2016. Although most studies have revealed no detectable effect of bleeding on fitness, Brown and Brown (2009) found that Cliff Swallows (Petrochelidon pyrrhonota) that were bled were 21-33% less likely to return the following year.…”
mentioning
confidence: 99%
“…Accounting for relatively minor levels of lack-of-fit has been commonly used in survival analyses, including in recent papers published on long-lived birds (e.g. Guillemain et al 2015).…”
Section: Survival Analysismentioning
confidence: 99%
“…Banding of birds for the purposes of population monitoring and individual identification is an ubiquitous ornithological practice that has proven extremely helpful to assess demographic parameters of countless wild bird populations (Santoro, Green & Figuerola, 2016; Champagnon et al, 2018). However, before committing resources and substantial efforts to start using them, it is important to not only assess issues like whether the fitted devices lead to reliable demographic parameters, but also that the banding operations themselves do not compromise survival and reproduction in any meaningful way (Saraux et al, 2011; Spotswood et al, 2012; Griesser et al, 2012; Guillemain et al., 2015a; Guillemain et al, 2015b; Weiser et al, 2016; Stein et al, 2017; Avila-Villegas, 2018; Border et al, 2018). We advocate that any study involving manipulation of animals should consider potential adverse effects based on the literature first.…”
Section: Discussionmentioning
confidence: 99%